Examining the impact of entrepreneurial psychology on agribusiness sustainability - Aliu, Mukhtar Mayowa; Jimoh, Abdulmalik; Okeme, Patrick (UIR Press, 2026)
Purpose: This study investigates the relationship between entrepreneurial Cognition (EC), entrepreneurial subjective norms (ESN), entrepreneurial self-efficacy (ESE), and entrepreneurial Innovation Capability (EIC) on agribusiness sustainability (AS) in North-Central Nigeria. Design/methodology/approach: Adopting a cross-sectional survey of 340 agro-processing firms, collected data were analyzed using Partial Least Square Structural Equation Modelling (PLS-SEM). Findings: Results revealed that EC and ESN exerted significant positive effects on agribusiness sustainability, while EIC served as a partial mediator between the constructs and AS. Furthermore, EC, ESE, and ESN significantly predicted EIC, indicating that innovation capability is largely shaped by entrepreneurs’ networks and competencies. Indirect effect analysis confirmed that EIC significantly mediates the relationships between EC, ESE, ESN, and AS. Limitations and Research implications: This study only examines the impact of entrepreneurial psychology on agribusiness sustainability in North Central Nigeria, caution should be exercised when generalizing the findings. Practical Implications: The study findings practically imply that enhancing entrepreneurial psychology strengthens agribusiness sustainability outcomes, hence recommends that targeted agribusiness capacity programs should be aimed at boosting entrepreneurial innovation capability to increase the sustainability of agribusinesses in North Central Nigeria. Originality/value: The findings from the PLS-SEM analysis demonstrate a statistically significant and positive relationship between entrepreneurial factors and agribusiness sustainability in North Central Nigeria.